Cytokine-induced killer cells targeted by the novel bispecific antibody CD19xCD5 (HD37xT5.16) efficiently lyse B-lymphoma cells - Tita-Nwa, Dinga Nkom Freddy; Moldenhauer, Gerhard; Herbst, Markus; Kleist, Christian; Ho, Anthony Dick; Kornacker, Martin (Cancer immunology immunotherapy, 2007)
Due to their dual binding capacity, bispecific antibodies (bsAb) can be used to cross-link cytotoxic effector cells with malignant targets and may thereby improve adoptive immunotherapy. In this study, the development and preclinical testing of the quadroma-derived bsAb HD37xT5.16 of the specificity CD19xCD5 is reported. Effector cells used were a population of ex vivo expanded and activated T cells called cytokine-induced killer (CIK) cells expressing CD5. When combined with CIK cells, the cytolytic potency of HD37xT5.16 against CD19 positive B cell lymphoma lines was comparable to that observed with a previously described CD19xCD3 bsAb. Further on, we could demonstrate that bsAb CD19xCD5, in contrast to its CD3-binding counterpart, does not induce proliferation of resting T cells and causes only little activation-induced cell death. Therefore, this novel bsAb binding effector T cells via CD5 may be particularly useful in combination with adoptive transfer of ex vivo activated T cells, e.g., in the setting of adoptive immunotherapy after allogeneic stem cell transplantation. The in vitro studies outlined here support the experimental use of bsAb HD37xT5.16 in preclinical in vivo models for evaluation of its safety and efficacy profile.
Gesehen am 20.10.2021